Full-scale vacuum degassing of activated sludge – A case study over 2-years of operation. (June 2021) - Gnida, Anna; Student, Sebastian
Graphical abstract: Highlights: sludge vacuum degassing improves sludge settling. very good sludge settling allows increasing the amount of biomass in the bioreactor. the use of sludge degassing results in better wastewater treatment efficiency. sludge production from gram of COD is 20 % lower when using vacuum degassing. Abstract: The effect of vacuum degassing of activated sludge on biological wastewater treatment over a total period of 4 years was examined. In half of the period studied, the treatment system was classic, where wastewater, after a biological reactor with nitrification-denitrification and biological dephosphatation, was directed to secondary settlers. In the second period, the treatment system was modified so that the sludge from the biological reactor was directed to the vacuum degasser, followed by the secondary settling tanks (vacuum degassing activated sludge system; VDAS). As a result of using the VDAS, a significant improvement in sludge settling ability was recorded, which allowed the plant operators to increase the amount of biomass in the biological reactor. Differences in the quantity and quality of the wastewater influent were found during both periods. However, the quality of treated wastewater and the efficiencies of nutrient removal and removal rates were usually better in the system with vacuum degassing. An improvement was achieved not only for the elimination of the different forms of nitrogen, which by definition were to be removed as ammonia and gaseous nitrogen, but also for organic compounds expressed as COD and phosphorus. As a result of the lower sludge loading, sludge production expressed in g SS per g COD removed was significantly lower (20 %) with the VDAS.